2013
DOI: 10.1080/00028487.2013.793613
|View full text |Cite
|
Sign up to set email alerts
|

Coding Gene Single Nucleotide Polymorphism Population Genetics of Nonnative Brook Trout: The Ghost of Introductions Past

Abstract: Fish have been translocated throughout the world, and introductions often have been executed repeatedly and have used mixtures of different strains from the native range. This history might have contributed to their invasive potential by allowing introduced and invading populations to circumvent expected reductions in genetic diversity from founder effects in a scenario termed the "genetic paradox" of invasions. We characterize patterns of genetic diversity in nonnative Brook Trout Salvelinus fontinalis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…For Brook Charr, Paradise Hatchery from North America was a probable source stock representing Lago Fagnano and Alonso River in the extreme southern end of Patagonia. This was consistent with expectations that Paradise Hatchery would be a possible source stock as it has been identified as a common source for broad introductions in other geographic regions outside the species’ range (Neville & Bernatchez, ). The other collections of Brook Charr from Patagonia were highly distinct from those in the native range in Quebec, Canada, which is consistent with the high level of genetic divergence commonly observed in this species (e.g., Marie et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…For Brook Charr, Paradise Hatchery from North America was a probable source stock representing Lago Fagnano and Alonso River in the extreme southern end of Patagonia. This was consistent with expectations that Paradise Hatchery would be a possible source stock as it has been identified as a common source for broad introductions in other geographic regions outside the species’ range (Neville & Bernatchez, ). The other collections of Brook Charr from Patagonia were highly distinct from those in the native range in Quebec, Canada, which is consistent with the high level of genetic divergence commonly observed in this species (e.g., Marie et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Our LD N b results are in line with findings showing higher genetic diversity for Lake Llanquihue and lower genetic diversity for Lake TLS. Artificially propagated populations resulting from multiple introduction events may show effective population sizes greater than naturally propagated ones as seen in introduced vendace Coregonus albula in Europe (Præbel et al., ) and brook trout in North America (Neville & Bernatchez, ). However, Narum et al.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates for the effective number of breeders using LD (N b ) were larger for rainbow trout from Lake Llanquihue than from Lake TLS. (Praebel et al, 2013) and brook trout in North America (Neville & Bernatchez, 2013). However, Narum et al (2017) recently found that estimates of LD N b among Chinook salmon Oncorhynchus tshawytscha populations introduced in Patagonia were smaller than among native populations, suggesting that there may be exceptions to these findings.…”
Section: Effective Number Of Breeders (Ld N B )mentioning
confidence: 99%
“…Brook Trout were abundant in the high-gradient, cold streams, whereas Cutthroat Trout and Rainbow Trout were abundant only in the moderate-gradient, cold sites that we sampled, a pattern also observed by Maret et al (1997) for least-disturbed streams in the upper Snake River basin. The mechanisms driving patterns of salmonid relative abundances requires further study, as those patterns could reflect negative competitive interactions (Peterson et al 2004;Benjamin et al 2011), hybridization (Meyer et al 2006), and stocking and invasion history (Benjamin et al 2007;Neville and Bernatchez 2013). Inconsistent capture of Rainbow Trout suggests this species has invaded only the lower portion of the watershed in streams nearest Lower Goose Creek Reservoir.…”
Section: Discussionmentioning
confidence: 99%